TRANSPARENCY AS THE OFFERED SOCIAL SERVICES IN THE ESTONIAN LOCAL GOVERNMENT - Vaike, Raudava (European Scientific Journal, ESJ, 2015)
The aim of the article has been pointed out, what are the main challenges arise from the interaction between the transparency and the structure of the social welfare administration. Used the organizational change theory, originally Mintzberg 1979, (Ferlie & Geraghty 2007) and followed the local government`s duties, however, the function of the decision-making process takes in. The strategy of research (methodology) utilised was the collective case study, I followed the information-oriented selection, triangulation has been used as a mixed method of acquiring data. According to the result, there the five challenges existing: 1) The social work profession does not regulate as the profession in the local government, however, the position is the ambivalent and without the professional power; 2) The structure of administration is involving the non-professionals, who are professionals in another field or the about non-educated members; 3) The decision-making process regarding the clients is distributed among different levels; 4) The practice undermines the independence of the social worker, and the social worker cannot protect the rights of the client; 5) The biggest challenge, reflect at the cases, the decision at the client level is politicized. Therefore, I argue, that the Social Affairs Committee or Social Affairs Committee of Municipal Government, the units of the administration of welfare in the local government, they act not necessary.